ҒӘРЕЗСИЗЛИК ДӘЎИРИ ҚАРАҚАЛПАҚ ӘДЕБИЯТЫ РАЎАЖЛАНЫЎЫНЫҢ БАСЛЫ БАҒДАРЛАРЫ - Алламбергенов, К. (FAN va JAMIYAT, 2016)
The article deals with the study of development ways of Karakalpak literature at the period of Independence. There have been analyzed many genres of literarure on the foreground of social-political, economical, cultural and spiritual changes and the main trends of development, changes in a genre and form. The author of the article comes to the conclusion that Karakalpak literature of the period of Independence has its main trends, it is on the way of free development and turned into the independent national literature.